2020
DOI: 10.1038/s41598-020-73484-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurements and modelling of viscosity and density of calcium and potassium chlorides ternary solutions

Abstract: Measured viscosity and density data for ternary aqueous solutions of CaCl2 and KCl are presented at temperatures between 293 and 323 K with 5 K increment. A modified Jones–Dole was introduced by adding extra terms and proved to be suitable for modelling of the viscosity data. Goldsack and Franchetto, Hu and Exponential models are used to correlate the viscosity data, too. Al models are correlated as a function of temperature and concentration. All models had successfully predicted the viscosity with high preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Additionally, electrolyte ions compete more fiercely for available water molecules, so the actual concentration of the electrolyte should be larger, leading to an underestimation of the calculated values. Arshad [11] introduced an ionic interaction parameter (G) into the equation to reduce this deviation. This method was used in this study to improve the equation for the quinary system solution as shown in Eq.…”
Section: Modified Extended Jones-dole Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, electrolyte ions compete more fiercely for available water molecules, so the actual concentration of the electrolyte should be larger, leading to an underestimation of the calculated values. Arshad [11] introduced an ionic interaction parameter (G) into the equation to reduce this deviation. This method was used in this study to improve the equation for the quinary system solution as shown in Eq.…”
Section: Modified Extended Jones-dole Modelmentioning
confidence: 99%
“…Zhang and Han [10] incorporated the 3.5th term of molar concentration into the Kaminsky extended formula, which can effectively represent very high or even saturated concentrations of NaCl solution. Arshad et al [11] successfully represented the viscosity of concentrated solutions of KCl and CaCl2 by incorporating higher order concentration terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individually, cations such as K + or Ca 2+ released from the hydration process can interact with water molecules and form more hydrogen bonds among water molecules, creating a closer distance among molecules in pore solutions. 17,18 As a result, the viscosity of the aqueous phase, in theory, would be increased to a certain degree, 19 which leads to the higher viscosity of cement suspension, according to Einstein's equation in theory. 20,21 Besides, the increase in ionic strength in the early stage in pore solution can also implement the shielding effect and result in a shorter range of Debye length, 22,23 which undermines the possible electrostatic force among particles and then increases the yield stress of a system.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of ions and non‐absorbed polymers and their interactions in the aqueous phase would lead to multiple effects on the system of a cement‐based material with resting time. Individually, cations such as K + or Ca 2+ released from the hydration process can interact with water molecules and form more hydrogen bonds among water molecules, creating a closer distance among molecules in pore solutions 17,18 . As a result, the viscosity of the aqueous phase, in theory, would be increased to a certain degree, 19 which leads to the higher viscosity of cement suspension, according to Einstein's equation in theory 20,21 .…”
Section: Introductionmentioning
confidence: 99%